Management of second trimester abortion beyond 20 weeks in a tertiary care setting - Yadav, Reetu; Rani, Reena; Sharma, Rachna; Rini, K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Management of second-trimester abortion beyond 20 weeks is still unclear. To analyse the management of second-trimester abortions in a tertiary care setting. Methods: A retrospective analysis was carried out over 1 year for the women undergoing 2nd trimester abortion after 20 weeks. The primary outcome was to find out the various regimens used for 2nd-trimester abortion. The secondary outcomes were the number of doses of drug required for completion of the abortion process, complications and side effects associated with the same. Other outcomes like the cause of abortion requirement beyond 20 weeks and the demographic profile of women have been noted. A review of literature was carried out on the management of 2nd trimester abortion beyond 20 weeks. Results: A total of 57 medical termination of pregnancy (MTP) were carried out. Mifepristone followed by misoprostol was the method of choice in 93% of cases. Other methods adopted were foleys induction, mifepristone alone. The mean number of misoprostol doses used in termination between 20-24 weeks were 3-4 (400 mcg), While it was 4-5 doses (200mcg) beyond 24 weeks of gestation. Hysterotomy and hysterectomy were done as a result of complication arising out of the regimen followed in less than 1 % of cases. Conclusions: The combination of 200 mg mifepristone and vaginally administered misoprostol is a safe, effective and non-invasive regimen for termination of pregnancy even beyond 20 weeks.